2015
DOI: 10.1177/1753465815603659
|View full text |Cite
|
Sign up to set email alerts
|

Health economic modeling of the potential cost saving effects of Neurally Adjusted Ventilator Assist

Abstract: This study showed economically favorable results for NAVA versus PSV. Our results show that only a minor decrease in the proportion of asynchronous patients with NAVA is needed for investments to pay off and generate savings. Future studies need to confirm this result by directly relating improved synchrony to the number of days on MV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Such a trial would be based on the assumptions above that improved patient‐ventilation interaction leads to decreased used of sedation and then into decreased number of mechanical ventilation days and decreased the length of intensive care unit days. Hjelmgren et al suspected this would hold true and developed a decision analytical model that associated the state of synchrony/asynchrony with a specified duration of mechanical ventilation days and a corresponding daily cost in the intensive care unit. They concluded that a minor decrease in the proportion of asynchrony in intensive care unit patients with NAVA would result in a decrease in mechanical ventilation days and result in cost savings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such a trial would be based on the assumptions above that improved patient‐ventilation interaction leads to decreased used of sedation and then into decreased number of mechanical ventilation days and decreased the length of intensive care unit days. Hjelmgren et al suspected this would hold true and developed a decision analytical model that associated the state of synchrony/asynchrony with a specified duration of mechanical ventilation days and a corresponding daily cost in the intensive care unit. They concluded that a minor decrease in the proportion of asynchrony in intensive care unit patients with NAVA would result in a decrease in mechanical ventilation days and result in cost savings.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that a minor decrease in the proportion of asynchrony in intensive care unit patients with NAVA would result in a decrease in mechanical ventilation days and result in cost savings. Hjelmgren et al utilized data from previous clinical studies as well as a Swedish intensive care registry for their cost modeling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is beyond the realms of feasibility, and so model outputs are compared with previously reported values. In 2015, Hjelmgren et al considered the cost consequence of neutrally-adjusted ventilatory assist (NAVA) mechanical ventilation relative to PSV in the Swedish setting ( 39 ). Their model varied substantially from that presented here, not considering future healthcare costs or any items outside of the ICU.…”
Section: Discussionmentioning
confidence: 99%